2020
DOI: 10.1520/gtj20190282
|View full text |Cite
|
Sign up to set email alerts
|

Compression and Shear Strength Characteristics of Unsaturated Intact Loess in True Triaxial Tests

Abstract: Previous studies of shear behavior from suction-controlled direct shear tests or triaxial tests focused mainly on remolded soils. Limited attention has been paid to suction measuring on unsaturated intact soil. In this paper, two series of saturated drained tests and unsaturated constant water content (CW) tests containing isotropic consolidation and shear tests with different intermediate principal stress parameters b were conducted to investigate deformation and shear strength characteristics of intact loess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…The mechanical properties of soil such as structural strength, shear strength, cohesion and internal friction angle are mainly affected by soil type, dry density and water content of soil. Dang et al [50][51] analyzed the influence of water content on the strength of unsaturated loess, gave a method to determine the structural strength of loess, and pointed out that the structural strength of unsaturated loess can be measured by the strength lost after its natural structure is destroyed, and there is a power function relationship between the structural strength and the initial water content; There is a good linear relationship between structural strength and unstable cohesion; The concept of ultimate strength moisture content of unsaturated loess is proposed. Zhang et al [52] took the Loess in Yangling area as the research object, and found that with the increase of water content, its structural strength and shear strength showed a decreasing trend, but the ratio of shear strength to structural strength basically remained unchanged, and the cohesion of unsaturated loess was negatively correlated with water content.…”
Section: Research Progress On Factors Affecting Gravity Erosion and I...mentioning
confidence: 99%
“…The mechanical properties of soil such as structural strength, shear strength, cohesion and internal friction angle are mainly affected by soil type, dry density and water content of soil. Dang et al [50][51] analyzed the influence of water content on the strength of unsaturated loess, gave a method to determine the structural strength of loess, and pointed out that the structural strength of unsaturated loess can be measured by the strength lost after its natural structure is destroyed, and there is a power function relationship between the structural strength and the initial water content; There is a good linear relationship between structural strength and unstable cohesion; The concept of ultimate strength moisture content of unsaturated loess is proposed. Zhang et al [52] took the Loess in Yangling area as the research object, and found that with the increase of water content, its structural strength and shear strength showed a decreasing trend, but the ratio of shear strength to structural strength basically remained unchanged, and the cohesion of unsaturated loess was negatively correlated with water content.…”
Section: Research Progress On Factors Affecting Gravity Erosion and I...mentioning
confidence: 99%
“…With the confining pressure of 20 kPa, the water content is 7.5%, degree of compaction is 96%, initial static deviatoric stress is 0 kPa, loading frequency is 1 Hz and 2 Hz, respectively,N lg f d scurve is shown in figure 12(d).With confining pressure of 20 kPa, water content is 7.5%, loading frequency is 1 Hz, degree of compaction is 96%, and initial static deviatory stress is 0 kPa and 10 kPa, respectively,N lg f d s -curve is shown in figure12(e). Similar to the calculation model between dynamic strength and vibration number, Wang et al have proposed the calculation model between the dynamic strength and vibration number of loess[21], as shown in equation (1).…”
mentioning
confidence: 99%